2011
DOI: 10.1155/2011/268214
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of XMRV Nucleic Acid and Antibody in HIV-1-Infected Men and in Men at Risk for HIV-1 Infection

Abstract: Xenotropic MLV-Related Virus (XMRV) was recently reported to be associated with prostate cancer and chronic fatigue syndrome (CFS). Infection was also reported in 3.7% of healthy individuals. These highly reported frequencies of infection prompted concerns about the possibility of a new, widespread retroviral epidemic. The Multicenter AIDS Cohort Study (MACS) provides an opportunity to assess the prevalence of XMRV infection and its association with HIV-1 infection among men who have sex with men. Reliable det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…However, in this study, no XMRV antibodies were detected in the 100 HIV‐1–seropositive blood donors from Cameroon. Zero or low levels of seroreactivity have been reported in HIV‐1–infected Spanish subjects (0%, 0/149) and US multicenter AIDS cohort patients (0.9%, 3/332) 28 (M. Arredondo, J. Hackett Jr, F. de Bethencourt, A. Treviñ, D. Escudero, A. Collado, X. Qiu, P. Swanson, V. Soriano, C. Carmen de Mendoza, manuscript in preparation). These serologic results are consistent with several other studies that have failed to detect XMRV DNA or RNA in HIV‐1–infected patients from Europe, United States, and Africa 29‐33 .…”
Section: Discussionsupporting
confidence: 91%
“…However, in this study, no XMRV antibodies were detected in the 100 HIV‐1–seropositive blood donors from Cameroon. Zero or low levels of seroreactivity have been reported in HIV‐1–infected Spanish subjects (0%, 0/149) and US multicenter AIDS cohort patients (0.9%, 3/332) 28 (M. Arredondo, J. Hackett Jr, F. de Bethencourt, A. Treviñ, D. Escudero, A. Collado, X. Qiu, P. Swanson, V. Soriano, C. Carmen de Mendoza, manuscript in preparation). These serologic results are consistent with several other studies that have failed to detect XMRV DNA or RNA in HIV‐1–infected patients from Europe, United States, and Africa 29‐33 .…”
Section: Discussionsupporting
confidence: 91%
“…Any sample that gave a signal equal to or greater than the cutoff value (Log N S/CO≥0.0) was repeated in duplicate, and samples with repeatedly reactive results were further analyzed by the ARCHITECT XMRV p30 CMIA for antibodies to capsid protein. Repeat reactivity (Log N S/CO≥0.0) to all three proteins is required to confirm a positive antibody finding [67] , [68] , [71] .…”
Section: Methodsmentioning
confidence: 99%
“…[ 2 4 5 6 ] As some studies have found XMRV in up to 87% of patients and others have failed to detect XMRV infection either in the patient cohorts or in the general population, the correlation between XMRV and human diseases has remained controversial. [ 7 8 9 ]…”
Section: Introductionmentioning
confidence: 99%